2013
DOI: 10.1063/1.4821608
|View full text |Cite
|
Sign up to set email alerts
|

Temporal structure of double plasma frequency emission of thin beam-heated plasma

Abstract: In the work presented here dynamics of spiky microwave emission of a beam-heated plasma near the double plasma frequency in ∼100 GHz band was studied. The plasma is heated by 80 keV, ∼2 MW, sub-ms electron beam that is injected into the multiple-mirror trap GOL-3. The beam-heated plasma diameter is of the order of the emitted wavelength. Modulation of individual emission spikes in the microwave radiation is found. The radiation dynamics observed can be attributed to a small number of compact emitting zones tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…We will mainly focus on generation of electromagnetic (EM) waves in the spatially bounded plasmas typical to beamplasma experiments in mirror traps [10][11][12]. It has been experimentally found that reducing in plasma thickness down to the radiation wavelength is accompanied by the substantial increase in the radiation efficiency [13].…”
Section: Introductionmentioning
confidence: 99%
“…We will mainly focus on generation of electromagnetic (EM) waves in the spatially bounded plasmas typical to beamplasma experiments in mirror traps [10][11][12]. It has been experimentally found that reducing in plasma thickness down to the radiation wavelength is accompanied by the substantial increase in the radiation efficiency [13].…”
Section: Introductionmentioning
confidence: 99%
“…Rr, 52.35.Qz Beam-plasma interaction plays an important role in various physical phenomena such as transport of relativistic electrons in the fast ignition scheme of inertial fusion, gamma-bursts, solar type II and III radio bursts, and collisionless shock waves in the space plasma (see review [1] and references therein). Also, beam-plasma collective interaction determines the efficiency of turbulent plasma heating [2,3] and electromagnetic emission [4][5][6][7] in fusion-oriented mirror traps.One of the most popular and effective tools for theoretical studies of the beam-plasma interaction is numerical simulations by the Particle-In-Cell (PIC) method. At present there is a great number of one-, two-, and three-dimensional PIC codes developed.…”
mentioning
confidence: 99%
“…Also, beam-plasma collective interaction determines the efficiency of turbulent plasma heating [2,3] and electromagnetic emission [4][5][6][7] in fusion-oriented mirror traps.…”
mentioning
confidence: 99%
“…Now, we use SAL to solve a real applied problem of calculating the power of electromagnetic radiation generated in a plasma‐electron beam system . Recent experiments with the GOL‐3 facility have shown that the radiation efficiency of electromagnetic waves (0.1‐0.5 THz) increases (approximately 1 % ) when the transverse sizes of the system are comparable with the length of radiated waves. Linear theory predicted a mechanism of plasma antenna in which continuous injection of a beam into a plasma channel with preliminary longitudinal density modulation provides high efficiency (up to 10%) of radiation generation at the plasma frequency.…”
Section: Antenna Generation Of Electromagnetic Radiation In Electron mentioning
confidence: 99%